Strategic Withholding through Production Failures - Sara Fogelberg; Ewa Lazarczyk (Research Institute of Industrial Economics (IFN), 2014)
Anecdotal evidence indicates that electricity producers use production failures to disguise strategic reductions of capacity in order to influence prices, but systematic evidence is lacking. We use a quasi-experimental set up and data from the Swedish energy market to examine such behavior. In a market without strategic withholding, the decision of reporting a failure should be independent of the market price. We show that marginal producers in fact base their decision to report a failure in part on prices, which indicates that failures are a result of economic incentives as well as of technical problems.
Keywords: L49; L94; 330; Electricity markets; Urgent Market Messages (UMMs); Unplanned failures